2006
DOI: 10.1159/000097797
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Intraoperative eCAP Thresholds and Postoperative Psychoacoustic Levels as a Prognostic Tool in Evaluating the Rehabilitation of Cochlear Implantees

Abstract: A sufficient correlation between objective (e.g. eCAP of the auditory nerve) and psychoacoustic data has not yet been possible due to high interindividual variability in cochlear implantees. Therefore, the application of objective data in the evaluation of speech rehabilitation after cochlear implantation was investigated. eCaps of all electrodes were measured intraoperatively. The ‘threshold’ and ‘comfort’ levels, speech recognition and pure tone thresholds were determined at follow-up. The correlation coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…After the removal of duplicates and screening of titles and abstracts, 143 remained. Evaluation of full texts yielded a total of 26 articles and cross‐referencing added one, resulting in a total of 27 relevant articles suitable for critical appraisal describing a relation between speech perception of cochlear implantees and characteristics of the recorded eCAPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the removal of duplicates and screening of titles and abstracts, 143 remained. Evaluation of full texts yielded a total of 26 articles and cross‐referencing added one, resulting in a total of 27 relevant articles suitable for critical appraisal describing a relation between speech perception of cochlear implantees and characteristics of the recorded eCAPs.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (2011) was excluded due to the absence of statistical methods investigating the correlation of interest . Basta et al (2007) was excluded because of the not solely electrophysiological parameter that was correlated to speech perception; a correlation between a psychophysical parameter and the electrophysiological parameter was used . The remaining 25 articles were eligible for further analysis …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 55 dB SPL the differences were no longer significant. The study by Basta et al [16] indicates significantly better correlations for patients with good speech comprehension. For the use of NRT in the clinical routine, it needs to be pointed out that the absolute NRT thresholds are not as important as the NRT threshold profile.…”
Section: Discussionmentioning
confidence: 89%
“…Their results correlate very well with those of a visual threshold determination; however, on account of the poor signal-to-noise ratio, the thresholds lay completely within the patients' range of auditory perceptionin some cases even above the C level. Other workers [6,10,15,16] therefore extrapolated the amplitude growth function (AGF) linearly, to calculate the stimulation strength at zero amplitude as the TNRT value. Müller-Deile and Morsnowski [17] found that the thresholds determined by AutoNRT were on average 6 CL lower than those determined by linear extrapolation.…”
Section: Discussionmentioning
confidence: 99%